Bilateral palsy of the vocal cords after COVID-19 infection - Jungbauer, Frederic; Hülse, Carl Roland; Lu, Fei; Ludwig, Sonja; Held, Valentin; Rotter, Nicole; Schell, Angela (Frontiers in neurology, 2021)
During the COVID-19 pandemic, adverse neurological effects have been described. In addition to unspecific neurological symptoms, cranial nerve deficits have appeared as part of SARS-CoV-2 infection. In this case report, we describe a 74-year-old patient who developed bilateral paralysis of the vocal cords some weeks following his dismissal in stable condition after COVID-19 pneumonia. After ruling out central lesions, peripheral tumors, and other possible causes, therapy was initiated with methylprednisolone, inhalations, and oxygen. The patient showed no improvement, so laterofixation after Lichtenberger was performed. The dyspnea worsened after several weeks, so a laser posterior cordectomy was performed with satisfactory outcome.
Gesehen am 06.10.2021